CHARACTERISTICS OF AIRBORNE MICROPLASTIC POLYMERS USING PASSIVE SAMPLING AND THE INFLUENCE OF METEOROLOGICAL CONDITIONS - Sasmita, Aryo; Priyambada, Gunadi; Ikhsandi, Ahmad (LPPM Universitas Jambi, 2026)
Tenayan Industrial Estate has various anthropogenic activities, including industrial and population-related activities. Many activities can affect the levels of pollutants in the air, including microplastics. Microplastics can be transported through the air by meteorological factors. This research examined the abundance of microplastic particles in ambient air around the Tenayan Industrial Estate, focusing on the types and kinds of microplastic polymers. The air sampling method employed was passive sampling, conducted at three locations: upwind, downwind, and center, carried out every 7 days for 28 days. Microscopical method to determine the amount of abundance, the classification of microplastic polymer types and types. Differential Scanning Calorimetry (DSC) tests were conducted to determine the type of plastic. The research results show that the upwind point has an average weekly microplastic abundance of 64.00 ± 39.53 particles/liter. The central point is the average abundance of 69,5 ± 31,38 particles/liter. The downwind point has the highest average microplastic abundance of 81 ± 60,86 particles/liter. The dominant form of microplastics is fiber, accounting for 60,7%. The Microplastic polymer types identified are polyvinyl chloride, polycarbonate, and polyamide. The results showed that microplastic abundance was influenced by meteorological factors, specifically wind speed. Downwind locations, which are residential areas, have the highest microplastic abundance, indicating accumulation rather than directional transport.